2014
DOI: 10.1016/j.jpowsour.2013.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Using potassium catalytic gasification to improve the performance of solid oxide direct carbon fuel cells: Experimental characterization and elementary reaction modeling

Abstract: The performance of a solid oxide electrolyte direct carbon fuel cell (SO-DCFC) is limited by the slow carbon gasification kinetics at the typical operating temperatures of cell: 650-850 o C. To overcome such limitation, potassium salt is used as a catalyst to speed up the dry carbon gasification reactions, increasing the power density by five-fold at 700 -850 o C. The cell performance is shown to be sensitive to the bed temperature, emphasizing the role of gasification rates and that of CO production. Given th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The R o and R p of the cells both decrease with increasing temperature. The improvement of Boudouard gasification rate of fuels with increasing temperature leads to more sufficient supply of CO to the anode active sites, which favors the decrease of concentration polarization and the increase of output performance …”
Section: Resultsmentioning
confidence: 99%
“…The R o and R p of the cells both decrease with increasing temperature. The improvement of Boudouard gasification rate of fuels with increasing temperature leads to more sufficient supply of CO to the anode active sites, which favors the decrease of concentration polarization and the increase of output performance …”
Section: Resultsmentioning
confidence: 99%
“…showed that a potassium salt catalyst at a mass ratio of K:C=1:10 increased the rate of carbon gasification, resulting in a significantly higher power density. The power density of CF‐SOFCs with potassium carbonate infused in the carbon bed was approximately five times higher than that without a catalyst …”
Section: Materials and Structural Development Of The Anode In Cf‐sofcsmentioning
confidence: 96%
“…These systems use an aqueous hydroxide electrolyte and thus must operate at greatly elevated pressures in order to maintain the electrolyte as a liquid. Early work was carried out within autoclaves at 200 °C and 30 bar pressure with raw brown coal as the fuel [17]. The autoclave body was used as the anode with an iron rod used as the cathode.…”
Section: Aqueous Hydroxide Electrolyte Technologymentioning
confidence: 99%